Peri-operative renal morbidity secondary to gentamicin and flucloxacillin chemoprophylaxis for hip and knee arthroplasty. Issue 4 (November 2013) - Ross, AD; Boscainos, PJ; Malhas, A; Wigderowitz, C
Introduction: This retrospective cohort study uses serum creatinine levels to assess the effect of gentamicin and flucloxacillin on renal function in hip and knee arthroplasty patients. Methods: Serum creatinine levels were recorded pre-operatively and at two points post-operatively (sample 1 and sample 2) for all patients undergoing hip and knee arthroplasty. Either cefuroxime, or gentamicin and flucloxacillin were used for chemoprophylaxis. The Risk, Injury, Failure, Loss, End Stage classification was used to assess renal injury. Results: The differences in mean percentage change between the two groups were 5.86% ( p  = 0.077) and 11.34% ( p  = 0.030) at sample 1 and sample 2, respectively. Two patients (1.62%) receiving cefuroxime were exposed to renal risk or worse at some point. A total of nine patients (6.04%) receiving flucloxacillin and gentamicin were exposed to renal risk. Of these, three (2.01%) sustained renal injury and two (1.34%) sustained renal failure. The risk of being exposed to renal risk was 3.75 times greater for the gentamicin and flucloxacillin group. The risks of sustaining a significant deterioration of renal function were 1.9 and 17 times greater for the gentamicin and flucloxacillin group at the first and second post-operative samples, respectively. Discussion: Flucloxacillin and gentamicin significantly worsens renal function post-operatively compared with cefuroxime.